The modulatory effect of encapsulated bioactives and probiotics on gut microbiota: improving health status through functional food. Issue 1 (14th December 2022) - Bauer-Estrada, Katherine; Sandoval-Cuellar, Camilo; Rojas-Muñoz, Yesica; Quintanilla-Carvajal, Maria Ximena
Abstract : Gut microbiota can be a crucial factor of the host's health status. It could be improved by interaction with biocompounds and probiotics that can be encapsulated to survive GIT and food processing conditions allowing the modulation of this microbiota. Abstract : The gut microbiota can be a determining factor of the health status of the host by its association with some diseases. It is known that dietary intake can modulate this microbiota through the consumption of compounds like essential oils, unsaturated fatty acids, non-digestible fiber, and probiotics, among others. However, these kinds of compounds can be damaged in the gastrointestinal tract as they pass through it to reach the intestine. This is due to the aggressive and changing conditions of this tract. For this reason, to guarantee that compounds arrive in the intestine at an adequate concentration to exert a modulatory effect on the gut microbiota, encapsulation should be sought. In this paper, we review the current research on compounds that modulate the gut microbiota, the encapsulation techniques used to protect the compounds through the gastrointestinal tract, in vitro models of this tract, and how these encapsulates interact with the gut microbiota. Finally, an overview of the regulatory status of these encapsulates is presented. The key findings are that prebiotics are the best modulators of gut microbiota fermentation metabolites. Also, probiotics promote an increase of beneficial gut microorganisms, which in some cases promotes their fermentation metabolites as well. Spray drying, freeze drying, and electrodynamics are notable encapsulation techniques that permit high encapsulation efficiency, high viability, and, together with wall materials, a high degree of protection against gastrointestinal conditions, allowing controlled release in the intestine and exerting a modulatory effect on gut microbiota.